Interprofessional education involving medical and pharmacy students during transitions of care. Issue 3 (4th May 2017) - Vogler, Carrie; Arnoldi, Jennifer; Moose, Helen; Hingle, Susan T.
ABSTRACT: The transition of care from hospital to home is susceptible to clinical errors and adverse drug events. Despite this risk and the benefits of an interprofessional approach to patient care, medicine and pharmacy do not often collaborate during transitions of care. The purpose of this study was to evaluate the impact of an interprofessional education experience consisting of medical and pharmacy students performing transitions of care. A total of 88 students (13 pharmacy students and 75 medical students) participated and were surveyed before and after the experience, to evaluate their confidence in performing aspects of the transition of care process as well as their attitudes towards interprofessional care. Pharmacy students had higher baseline levels of confidence compared with the medical students, and both student groups revealed a significantly greater level of confidence in their abilities after the experience. The impact of the experience on students' attitudes towards interprofessional care varied, with medical students showing very little change from baseline and pharmacy students showing improved attitudes in several areas. The results of this study have positive implications for an interprofessional approach to transitions of care while highlighting potential future areas of study.